Phase composition and microstructure of new Ti–Ta–Nb–Zr biomedical alloys prepared by mechanical alloying method. (8th February 2017) - Dercz, G.; Matuła, I.; Zubko, M.; Dercz, J.
Abstract : The study presents the results of the influence of high-energy ball-milling time on the structure of the new β -type Ti–Ta–Nb–Zr alloys for biomedical applications. Initial elemental powders were mechanically alloyed in a planetary high-energy ball mill at different milling times (from 10 to 90 h). Observation of the powder morphology after various stages of milling leads to the conclusion that with the increase of the milling time the size of the powder particles as well as the degree of aggregation change. Clear tendency of crystalline size reduction at every stage of the grinding process is clearly observed. The X-ray diffraction results confirmed the formation of β phase during high-energy ball milling of the precursor mixture of Ti, Ta, Nb, and Zr. The Rietveld refinement method has shown that both the production method and the atomic radii of the elements used in the mechanical synthesis have influence on the structure. Furthermore, it was found that a broadening of the diffraction peaks with increase of the milling time results from an increase in the crystallites dispersion and an enlargement in the lattice distortion. The results indicate that this technique is a powerful and high productive process for preparing new β -titanium alloys with nanocrystalline structure and appropriate morphology.